Transcendent Philosophy of Medicine: A Deductive Synthesis According to the Transcendental Wisdom (Mulla Sadra School of Thought) - Khajeazad, Mojtaba (Journal of religion and health, 2021)
Medicine is dependent to definition of human being in all existential dimensions, and this study attempts to synthesize a philosophy of medicine based on transcendental wisdom that was instituted by Mulla Sadra (979-1045 AH /1571-1635 AD). Using implication eliciting methodology, in the paradigm of consensual qualitative research, ten main principles of transcendental wisdom were selected and described after being approved by experts (n = 13). Then, after more than 4 years of prolonged engagement using these principles, the transcendent philosophy of medicine was deductively synthesized. Afterward, to reach consensus, the results were reviewed in four panel discussions with experts (n=20). According to the transcendental wisdom, human being has four main dimensions including corpus, psyche, nous and soul and each contain two core aspects. These dimensions and aspects construct a real unity complex called human being (Nafs), that is the survival agent and cause of all aware and unaware biological, cognitive and behavioral capabilities in all dimensions of human existence. A holistic model of health was presented, and coherent strategies according to the ten transcendental wisdom principles were recommended in all corporeal and incorporeal aspects of human health, including environmental, biological, mental, identity-related, logical, intellectual, spiritual, ethical and social health.